Corporate attention to social responsibility disclosures: a study of Malaysian companies - Mohd, Puzlah; Atan, Ruhaya; Zainon, Saunah (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2003)
This paper presents a study of corporate social disclosures by public companies listed on the main board of the Kuala Lumpur Stock Exchange (KLSE). In a sample of 92 companies ranked by market capitalization as at June 2001, the companies were classified into five major sectors namely trading and services, finance, consumer products, industrial products and others. There were 55 items of information listed for the purpose of this study and the items are categorised into items of information replaced to employees, customers, community and corporate governance. The results of the analysis revealed that about 45% of the companies disclosed below the mean score and only 13 companies disclosed more than 70% of the items of information listed in the study. Additional insights are given into the relationship between the company characteristics and the extent of corporate social responsibility disclosure. The results indicate there was significant relationship between the company size, company performance and the extent of disclosures.